Maternal risk factors and periodontal disease: A cross-sectional study among postpartum mothers in Tamil Nadu - Rohini Govindasamy; Manikandan Dhanasekaran; Sheeja S Varghese; V R Balaji; B Karthikeyan; Ananthi Christopher (Wolters Kluwer Medknow Publications, 2017)
Background and Aim: It is inconclusive that periodontitis is an independent risk factor for adverse pregnancy outcomes. This study aims to investigate the association between maternal periodontitis and preterm and/or low birth weight babies. Settings and Design: This was a prospective cross-sectional study. After prior informed consent, 3500 postpartum mothers were selected from various hospitals in Tamil Nadu and categorized into the following groups: group-1 - Normal term normal birth weight (n = 1100); Group-2 - Preterm normal birth weight (n = 400); Group-3 - preterm low birth weight (PTLBW) (n = 1000); and Group-4 - Normal term low birth weight (n = 1000). Periodontal examination was done, and risk factors were ascertained by means of questionnaire and medical records. Statistical Analysis: Comparison between case groups and control groups were done, odds ratio (OR) was calculated, and statistical significance were assessed by Chi-square tests. To control for the possible confounders, all variables with P < 0.05 were selected and entered into multivariate regression model, and OR and 95% confidence limits were again estimated. SPSS-15 software was used. Results: Periodontitis was diagnosed in 54.8%, 52.3%, 53.8%, 59.4%, respectively. On comparison between the groups, none of periodontal parameters showed significant association except for the crude association observed in Group-4 for mild periodontitis (OR - 1.561; P = 0.000) and PTLBW. Conclusion: Periodontitis is not a significant independent risk factor, and obstetric factors contribute a major risk for preterm and/or low birth weight babies